Piezo-Active Composites Microgeometry-Sensitivity Relations - Topolov, Vitaly Yu.; Bowen, Christopher R.; Bisegna, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is devoted to the systematic description of the role of microgeometry of modern piezo-active composites in the formation of their piezoelectric sensitivity. In five chapters, the authors analyse kinds of piezoelectric sensitivity for piezo-active composites with specific connectivity patterns and links between the microgeometric feature and piezoelectric response. Among connectivity elements to be discussed, of interest are 2-2, 1-3, 1-1, and 0-3. The role of components and microgeometric factors is discussed in the context of the piezoelectric properties and their anisotropy in the composites. Interrelations between different types of the piezoelectric coefficients are highlighted. The monograph fills a gap in piezoelectric materials science and provides readers with data on the piezoelectric performance of novel composite materials that are suitable for sensor, transducer, hydroacoustic, energy-harvesting, and other applications.
Preface -- Piezoelectric Medium and Piezoelectric Sensitivity -- Effective Piezoelectric Coefficients dij*: From Microgeometry to Anisotropy -- Microgeometry of Composites and Their Piezoelectric Coefficients gij* -- Piezoelectric Coefficients eij* and dij*: Combination of Properties at Specific Microgeometry -- Piezoelectric Coefficients eij* and hij*: Other Combination of Properties -- Ways to Improve Piezoelectric Sensitivity of Modern Piezo-active Composites. .
Keywords: Optical materials; Telecommunication; Semiconductors; Ceramic materials; Energy harvesting; Optical Materials; Microwaves, RF Engineering and Optical Communications; Semiconductors; Ceramics; Energy Harvesting